2021
DOI: 10.5603/fm.a2020.0097
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of local rosmarinic acid and topical dexpanthenol applications on wound healing in a rat experimental wound model

Abstract: We compared the effects of rosmarinic acid and dexpanthenol in a rat experimental wound model. Twenty-four Wistar albino rats weighing 200-250 g were randomly divided into 3 groups. After 2-cm full-thickness skin defects were created, the wounds were washed with sterile 0.9% NaCl solution. After washing, the control group was left untreated, the second group received 5% dexpanthenol cream, and the third group received 10% rosmarinic acid cream. Before excision, the skin was evaluated macroscopically by measuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
3
6
0
Order By: Relevance
“…Our results suggest that in a complex mixture of compounds, such as an EO, some compounds might antagonize the effect of carvacrol, thus decreasing its pro-migratory properties. Similar effects were reported for rosmarinic acid, promoting cell migration in wound models [148,149] and presenting an inhibitory effect in cancer cells [150][151][152][153][154]. Salvianolic acids A and B are known to induce [155][156][157][158][159] as well as to delay [160][161][162] cell migration.…”
Section: Discussionsupporting
confidence: 66%
“…Our results suggest that in a complex mixture of compounds, such as an EO, some compounds might antagonize the effect of carvacrol, thus decreasing its pro-migratory properties. Similar effects were reported for rosmarinic acid, promoting cell migration in wound models [148,149] and presenting an inhibitory effect in cancer cells [150][151][152][153][154]. Salvianolic acids A and B are known to induce [155][156][157][158][159] as well as to delay [160][161][162] cell migration.…”
Section: Discussionsupporting
confidence: 66%
“…As in this experiment, the full therapeutic effect was observed on the 14th day of treatment. The data obtained is also consistent with the results of the group of researchers (Küba et al, 2021). During an experimental assessment of dexpanthenol (5% ointment) efficacy on rats, the greatest reduction in wound size in the late postoperative phase was noted: from day 10 to day 14.…”
Section: Table 7 Dynamics Of Changes In the Area Of Wound Surfaces (M...supporting
confidence: 89%
“…Regarding isolated compounds, several studies have reported their wound healing capacities. Indeed, wound healing properties have been reported for rosmarinic acid [ 67 , 68 ], salvianolic acid A, and danshensu [ 69 , 70 , 71 , 72 ]. The aglycone apigenin also promotes in vitro and in vivo wound healing [ 73 , 74 , 75 , 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%